Hole Integrity Of Carbon Fiber Reinforced Epoxy Composites Using Combined Punching And Drilling Techniques - Abdullah, Mohd Safie (2019)
The use of the fiber reinforced polymer (FRP) has been increased in recent year in many industries, mostly in automotive, aircraft and marine structures due to strength to the weight ratio, better fatigue life, corrosion resistance and tailored-made properties. One of major advantage is that structure can be moulded easily to the net shape. However, there is still a need to joint to assemble the composite structures into the final product. This is essential when the design of the product is too complicated to be moulded into single part or the structure need a frequent inspection and replacement for maintenance. Therefore, to assemble the structures together, the use of mechanical joint in composite structures is inevitable. The capability of the mechanical joints (bolted joint, pin joints, and rivet joints) depends on the hole quality and performance since the load transmitted via fastener give rise to stress concentration around the hole-fastener boundary. Drilling is the most common technique in hole making technique of composite panel. But due to wear, quality of the produce hole is severely affected. At the same time cost will increase as the frequent regrinding is required. From previous study, punching was proposed. Wear problem is not an issue in punching, but hole quality become the major issue. This experimental study aims to investigate the quality of hole prepared via conventional drilling technique and the combined technique (punching + conventional drilling) on carbon fiber reinforced polymer (CFRP). The effect of the both hole making techniques (combined technique and conventional drilling) to the hole quality and performance were evaluated by conducting experimental based on surface roughness and bearing strength. The surface roughness measurement was performed over a sampling length of 3.6 mm along at the four quadrant points of the hole wall. A bearing test a was conducted using modified fixture. The failure modes resulting from an experiment are quantified and compared to literature. The results confirm that the use of the combined technique in hole making on CFRP is almost similar to the conventional drilling alone in terms of bearing strength and failure mode as well as surface roughness.